ANALYSIS OF WOMEN’S PARTICIPATION IN RAINFED RICE AGRICULTURAL SYSTEMS IN GEBANGANGKRIK VILLAGE OF NGIMBANG LAMONGAN, EAST JAVA - Eko Sutrisno; Poppy Diana Sari (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2016)
The aim of this study was to obtain in-depth information about the participation of women farmers in agricultural production in the village of Gebangangkrik. Women in the village of Gebangangkrik go to work in the fields to help their husbands, from land preparation to post harvest process. Fees earned by women is lower than for men. They work with a rotation system or alternately between families or between neighbors that do not receive fees or spend big except for breakfast. There are many women farmers who worked to pay the debt, because when the bad season come, they had to borrow rice to other people who had more extensive rice fields with the assurance will voluntarily to help work in the fields when the next planting season. However, women farmers access to information in the field of agriculture is still very limited, so it seems that the girls were just as workers.